Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1111/1467-9582.00099
|View full text |Cite
|
Sign up to set email alerts
|

Plural marking, indefiniteness, and the noun phrase

Abstract: This article proposes that plural marking on nouns in Persian is licensed only if those nouns are contained within D/QPs. This proposal accounts for why plural-marked nouns are construed as definite unless an overt marker of indefiniteness appears, and why plural marking does not cooccur with numerals unless the noun phrase is definite. It is also shown that the indefinite marker in Persian is quantitative rather than cardinal and is thus associated with higher functional structure within the noun phrase than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 19 publications
3
69
0
Order By: Relevance
“…It has often been observed that plural markers in classifier languages tend to be associated with definite readings, or that they occur more often in definite than indefinite contexts (e.g., Iljic 1994;Li 1999;Ghomeshi 2003), and this is often interpreted as meaning that the plural marker itself encodes definiteness. Moreover, in Korean literature, there seems to be underlying assumption that -tul marks definiteness.…”
Section: -Tul Is Not a Definiteness Markermentioning
confidence: 99%
See 1 more Smart Citation
“…It has often been observed that plural markers in classifier languages tend to be associated with definite readings, or that they occur more often in definite than indefinite contexts (e.g., Iljic 1994;Li 1999;Ghomeshi 2003), and this is often interpreted as meaning that the plural marker itself encodes definiteness. Moreover, in Korean literature, there seems to be underlying assumption that -tul marks definiteness.…”
Section: -Tul Is Not a Definiteness Markermentioning
confidence: 99%
“…For example, Ghomeshi (2003) shows that the Persian plural marker -ha does not itself encode definiteness. The Korean plural marker -tul behaves in a similar way, as illustrated in (27).…”
Section: -Tul Is Not a Definiteness Markermentioning
confidence: 99%
“…(1a) suggests that r ā is a definiteness marker, which has often been assumed (e.g. Ghomeshi 2003). However, the object marker also occurs with the indefinite markers yek and -i, leading to a specific interpretation, as in (19a,b) (Karimi 2003), and with indefinites in the restrictor of generic quantifiers, as in (19c,d) 'Vinegar curdles milk.'…”
Section: Pins As Event-dependent Definitesmentioning
confidence: 99%
“…L + H*h L + H* h L + H* lL% 4 The definite marker -e/-ae (sometimes realized as -he/-hae or -ye/-yae), used only in conversational style, attracts the primary lexical stress (Ghomeshi 2003 Figure 10). …”
Section: + H*h L + H*h L + H* L H%mentioning
confidence: 99%